(untitled) (Nigerian Journal of Technology, 2018)
This study investigates the effect of tyre steel fibres on compressive strength of hollow sandcrete blocks. A total of 36 number 450mm x 225mm x 225mm hollow sandcrete blocks with 0%, 1%, 2 %, and 3% of tyre steel fibre content were produced and tested for density, compressive strength and water absorption. From the test results, the densities of blocks increase with an increases in fibres contents. As at 28 days, the density increases from 1395.20 kg/m3 for 0% to 1425.57kg/m3 for 3% fibre content. Also, the water absorption decreases with increases in tyre steel fibres. Furthermore, the compressive strength increases with increase in tyre steel fibres contents. At 28 days, there was an increase in compressive strength of 6%, 58% and 95% for 1%, 2% and 3% fibre contents respectively. It is concluded that addition of tyre steel fibres significantly improves the performance of hollow sandcrete blocks. http://dx.doi.org/10.4314/njt.v37i4.3